Analisis Peran dan Fungsi Bank BNI dalam Meningkatkan Perekonomian Masyarakat dengan Menerapkan Sistem Kredit - Liu, Gracentya R. A Faku; Wea, Aqualina; Kabba, Melkianus Nedi (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This study analyzes the role and function of Bank BNI in improving the community's economy through a credit system. With a qualitative approach based on interviews, this study aims to explain Bank BNI's contribution to economic growth, especially in rural areas. The results show that Bank BNI plays an important role as a financial intermediary by channeling credit to support small and medium enterprises (SMEs). However, obstacles such as geographical distance and lack of public understanding of the credit process are challenges in the effectiveness of distribution. To overcome this, it is recommended that there be public education, improved service quality, and digital banking innovation. This study concludes that effective credit distribution has a significant impact on economic stability. Suggestions are aimed at improving customer service and community empowerment programs to maximize the benefits of the credit provided. These efforts are important to support sustainable economic growth, especially in areas that are still lagging behind.